New kinds of analytical solitary wave solutions for ionic currents on microtubules equation via two different techniques - Khater, Mostafa M. A.; Jhangeer, Adil; Rezazadeh, Hadi; Akinyemi, Lanre; Akbar, M. Ali; İnç, Mustafa; Ahmad, Hijaz (Springer, 2021)
In this survey, the ionic currents along the microtubules equation handled by applying two different techniques. It describes the ionic transport throughout the intracellular environment. This phenomenon explains the behavior of many applications in a biological nonlinear dispatch line for ionic currents. Using two different analytical techniques on this equation allows us to get new forms of analytical solitary traveling wave solutions. The obtained solutions support many researchers concerned with the discussion of the physical properties of the ionic currents along microtubules. Microtubules are one of the main components of the cytoskeleton, and function in many operations, comprehensive constitutional backing, intracellular transmit, and DNA division. The thing which makes us applies this property in many applications for this model. The earned results demonstrate that the proposed methods are significantly powerful, evangelist, relaxing, suitable, and convenient for solving many nonlinear models.
Keywords: Extended simple equation method; Generalized exp (-phi(xi))-expansion method; Ionic currents along micro-tubules equation